2009
DOI: 10.1074/jbc.m109.013813
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Splice Variants of HAS1 (Hyaluronan Synthase 1) Multimerize with and Modulate Normally Spliced HAS1 Protein

Abstract: Most human genes undergo alternative splicing, but aberrant splice forms are hallmarks of many cancers, usually resulting from mutations initiating abnormal exon skipping, intron retention, or the introduction of a new splice sites. We have identified a family of aberrant splice variants of HAS1 (the hyaluronan synthase 1 gene) in some B lineage cancers, characterized by exon skipping and/or partial intron retention events that occur either together or independently in different variants, apparently due to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 73 publications
(69 reference statements)
1
33
0
Order By: Relevance
“…Thus, the dimers are kept together by strong interactions. In a recent study it was demonstrated that HAS1 forms multimers through intermolecular disulfide bonds (36). However, the HAS2 dimers we observed were seen both in the presence and absence of reducing agents, making it unlikely that disulfide bonds are involved.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, the dimers are kept together by strong interactions. In a recent study it was demonstrated that HAS1 forms multimers through intermolecular disulfide bonds (36). However, the HAS2 dimers we observed were seen both in the presence and absence of reducing agents, making it unlikely that disulfide bonds are involved.…”
Section: Discussionmentioning
confidence: 66%
“…Aberrant splice variants of HAS1 are able to modulate expression of the normally spliced variant [25]. Abnormalities of the HA synthase enzymes have been associated with transformation and tumor metastases [2, 26].…”
Section: The Hyaluronan Synthasesmentioning
confidence: 99%
“…Several members of the hyaluronic acid (HA) family of molecules, HA synthases (i.e., HAS1, HAS2, HAS3), HA receptors (i.e., CD44 and RHAMM), and hyaluronidases (mainly HYAL-1), are critical determinants of tumor growth and progression (Adamia, Pilarski, Belch, & Pilarski, 2013; Ghosh, Kuppusamy, & Pilarski, 2009; Golshani et al, 2007; Karbownik & Nowak, 2013; Orian-Rousseau, 2010; Simpson & Lokeshwar, 2008; Sironen et al, 2011). HA family members promote malignant behavior of tumor cells in vitro , and tumor growth, metastasis, and angiogenesis in xenograft models (Bharadwaj et al, 2009; Chao, Muthukumar, & Herzberg, 2007; Gurski et al, 2012; Li, Li, Brown, & Heldin, 2007; Lokeshwar, Cerwinka, & Lokeshwar, 2005; Lokeshwar et al, 2006; Siiskonen, Poukka, Tyynela-Korhonen, Sironen, & Pasonen-Seppanen, 2013; Tan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental model systems such as breast, bladder, prostate, and colon, studies have been mainly focused on modulating the expression of individual HA family molecules and assessing their effects on tumor cell phenotypes both in vitro and in vivo . Each HA synthase or HYAL-1, either alone or coexpressed, contributes to tumor cell proliferation, motility, and invasion, and to enhanced tumor growth, metastasis, and angiogenesis in xenografts; in contrast, knockdown of these genes inhibits tumor cell functions (Adamia et al, 2013; Bharadwaj et al, 2009; Chao et al, 2007; Ghosh et al, 2009; Golshani et al, 2007; Li et al, 2007). In the case of HYAL-1, promotion of tumor cell function is dose dependent.…”
Section: Introductionmentioning
confidence: 99%